Private discourse or discourse on privacy? An intimate world of Internet posts’ authors - Kalisz, Aleksandra (Papers in Linguistics, 2021)
The article focuses on the category of privacy, whose traces are looked for in Internet posts published on the profile of a secret group formed in social media. The analysed research material reveals genological provenance of an Internet post, thus proving that virtual space, contrary to popular belief, is not an area filled with completely new genres of speech. What undergoes change is only the form of message, which is related to the media environment where the post is embedded. Thus, in the analysed Internet posts one can find well-known genre patterns applied to achieve particular communication intentions. The undertaken considerations also allow one to determine parameters of private discourse, and to perceive privacy that has been made public as a specific strategy of self-disclosure, more and more willingly used by social media users.